Distribution of two-component signal transduction systems BlpRH and ComDE across streptococcal species - Dhaked, Hemendra Pal Singh; Biswas, Indranil (Frontiers in Microbiology, 2022)
Two-component signal transduction (TCS) systems are important regulatory pathways in streptococci. A typical TCS encodes a membrane-anchored sensor kinase (SK) and a cytoplasmic response regulator (RR). Approximately, 20 different types of TCSs are encoded by various streptococci. Among them, two TCSs, in particular BlpRH and ComDE, are required for bacteriocins production and competence development. The SK component of these two TCSs is highly similar and belongs to the protein kinase-10 (HPK-10) subfamily. While these two TCSs are present in streptococci, no systematic studies have been done to differentiate between these two TCSs, and the existence of these pathways in several species of the genus Streptococcus is also unknown. The lack of information about these pathways misguided researchers for decades into believing that the Streptococcus mutans BlpRH system is a ComDE system. Here, we have attempted to distinguish between the BlpRH and ComDE systems based on the location of the chromosome, genomic arrangement, and conserved residues. Using the SyntTax and NCBI databases, we investigated the presence of both TCS systems in the genome of several streptococcal species. We noticed that the NCBI database did not have proper annotations for these pathways in several species, and many of them were wrongly annotated, such as CitS or DpiB instead of BlpH. Nevertheless, our critical analyses led us to classify streptococci into two groups: class A (only the BlpRH system) and class B (both the BlpRH and ComDE systems). Most of the streptococcal groups, including bovis, pyogenic, mutans, salivarius, and suis, encode only the BlpRH system. In contrast, only in the mitis and anginosus groups were both the TCS systems present. The focus of this review is to identify and differentiate between the BlpRH and ComDE systems, and discuss these two pathways in various streptococci.